2011
DOI: 10.1590/s1516-31802011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Budd-Chiari syndrome in association with Behçet's disease: review of the literature

Abstract: The risk that patients with Behçet's disease may develop various thrombotic complications has been previously described. Although vascular complications from Budd-Chiari syndrome associated with Behçet's disease have been described, the pathogenic mechanisms are still unknown. Severe vascular complications present in Budd-Chiari syndrome associated with Behçet's disease are very common among young male adults. The objective of this study was to review the literature and present the association of Budd-Chiari s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Early diagnosis is therefore important for patients with BCS to receive prompt and specific treatment (12). Furthermore, misdiagnosis may occur if the patient is not diagnosed with BD prior to BCS (8,9). Case 2 initially presented with symptoms of liver cirrhosis and was given non-specific treatment, but was diagnosed with BD 6 months later at The First Affiliated Hospital of Sun Yat-sen University.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early diagnosis is therefore important for patients with BCS to receive prompt and specific treatment (12). Furthermore, misdiagnosis may occur if the patient is not diagnosed with BD prior to BCS (8,9). Case 2 initially presented with symptoms of liver cirrhosis and was given non-specific treatment, but was diagnosed with BD 6 months later at The First Affiliated Hospital of Sun Yat-sen University.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ~5% of patients with BCS in western countries, 9% in Turkey and 13% in Egypt may be attributed to BD (69). However, misdiagnosis is a common occurrence in cases of BD associated BCS (BD-BCS) (8,9). Certain patients exhibit no overt symptoms and others experience abdominal pain, jaundice, nausea, enlarged liver/spleen and ascites (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Pasmant et al, 2010). In addition, thrombophlebitis, erythrocytosis, multiple myeloma, and positive antiphospholipid antibody due to long-term oral administration of contraceptives are other causes of these medical conditions (Carvalho et al, 2011;Yadav et al, 2012). Although the aforementioned studies have identified BCS manifested by hepatic venous obstruction due to thrombosis, they cannot provide an explanation for that manifested by MOVC.…”
Section: Discussionmentioning
confidence: 99%